Pengaruh Kekuatan Moral Wajib Pajak, Sanksi Pajak dan Tarif Pajak Terhadap Penghindaran Pajak Dikota Batam - Putriyani br Siboro; Dian Efriyenti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Taxes are a source of income for the government which is responsible for the administration and development of government. This research aims to assess the influence of Taxpayer Moral Strength, Tax Sanctions, and Tax Rates on Tax Avoidance. The method applied is quantitative, with a total research population of 100 students from the accounting study program in the city of Batam. The sample was obtained using the Slovin formula, which resulted in 99 respondents. The sampling method used was simple random sampling. Data collection was carried out using a questionnaire whose validity and reliability had been tested before distribution. Data analysis by applying multiple linear regression tests. The results of the analysis show that the Moral Strength of Taxpayers and Tax Rates have a negative but not significant influence on Tax Avoidance in the city of Batam. Meanwhile, Tax Sanctions have an influence but are not significant on Tax Avoidance in Batam City.